2006
DOI: 10.1210/jc.2006-0061
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Production Rate in Posttraumatic Stress Disorder

Abstract: The data indicate that PTSD in the chronic and unprovoked state is not characterized by an acute biological stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…The absence of group difference in ACTH levels is consistent with other negative studies of ACTH in PTSD (Kanter et al, 2001 ;Newport et al, 2004), and with a recent finding of similar cortisol production rates in PTSD patients and normal subjects (Wheler et al, 2006). Lower ACTH in women was found by Yehuda et al (2004), and is consistent with the theory that adrenal glands in women are more sensitive to ACTH (Horrock et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The absence of group difference in ACTH levels is consistent with other negative studies of ACTH in PTSD (Kanter et al, 2001 ;Newport et al, 2004), and with a recent finding of similar cortisol production rates in PTSD patients and normal subjects (Wheler et al, 2006). Lower ACTH in women was found by Yehuda et al (2004), and is consistent with the theory that adrenal glands in women are more sensitive to ACTH (Horrock et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the paucity of studies using multiple measures of stress over the life course, many did not include as many indicators of neuroendocrine system function as in the paper here and most made use of considerably smaller, non-population-based samples. Although it is difficult to summarize these varied papers, on the whole results appear mixed, with some supporting (Evans, 2003; Janicki-Deverts et al, 2007; Lemieux & Coe, 1995; Yehuda et al, 1995), some not supporting (Kubzansky et al, 1998; Powell et al, 2002) and others providing evidence for and against (Babisch, 2003; Luecken et al, 1997; Olff et al, 2006; Wheler et al, 2006) the connection between life stress and dysregulated neuroendocrine biomarker levels.…”
Section: Discussionmentioning
confidence: 99%
“…And although negative findings have also been found by others (Babisch et al, 2001; Powell et al, 2002), these studies typically have only examined one particular type of stressor (e.g., marital disruption or noise exposure) instead of multiple stressors that span the life course. A further limitation of these studies is that they have often investigated one particular biomarker (instead of a grouping representative of a physiological system or systems) and have been conducted on small, non-population-based samples (Babisch et al, 2001; Luecken et al, 1997; Powell et al, 2002; Wheler et al, 2006). In sum, there is a paucity of studies (the 2000 SEBAS and perhaps one or two others) that can claim to have tested in a rigorous way the hypothesis that markers of life history stress are correlated with higher levels of AL.…”
Section: Introductionmentioning
confidence: 99%
“…Data on baseline cortisol levels in PTSD have been somewhat inconsistent (see recent review by Yehuda, 2009), with several studies reporting low levels in PTSD (Yehuda et al, 1990, 2000; Young et al, 2004) and others finding no diagnostic differences (Shalev et al, 2008; Wheler et al, 2006). A recent meta-analysis concluded that cortisol levels were only reduced if serum or plasma levels were measured (Meewisse et al, 2007).…”
Section: Discussionmentioning
confidence: 99%